2017
DOI: 10.1021/acsami.7b02035
|View full text |Cite
|
Sign up to set email alerts
|

Monolith-Supported Amine-Functionalized Mg2(dobpdc) Adsorbents for CO2 Capture

Abstract: The potential of using an amine-functionalized metal organic framework (MOF), mmen-M(dobpdc) (M = Mg and Mn), supported on a structured monolith contactor for CO capture from simulated flue gas is explored. The stability of the unsupported MOF powders under humid conditions is explored using nitrogen physisorption and X-ray diffraction analysis before and after exposure to humidity. Based on its superior stability to humidity, mmen-Mg(dobpdc) is selected for further growth on a honeycomb cordierite monolith th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…A further design strategy that merits exploration is the controlled incorporation of defects in MOFs, such as what has been reported in the UiO-66(Hf) structure. [49] More generally, a fundamental understanding of MOF thermal expansion is crucial to advancing their utility in a wide range of potential applications that include coated monoliths, [50] microcantilever sensors, and electronic devices. [51] In each of these scenarios, changes in temperature will arise, and a mismatch in the CTE of the MOF and its substrate material will produce residual stresses that can lead to cracking and peeling behavior or compromise the adhesion between the MOF and its interfaced layer.…”
Section: Discussionmentioning
confidence: 99%
“…A further design strategy that merits exploration is the controlled incorporation of defects in MOFs, such as what has been reported in the UiO-66(Hf) structure. [49] More generally, a fundamental understanding of MOF thermal expansion is crucial to advancing their utility in a wide range of potential applications that include coated monoliths, [50] microcantilever sensors, and electronic devices. [51] In each of these scenarios, changes in temperature will arise, and a mismatch in the CTE of the MOF and its substrate material will produce residual stresses that can lead to cracking and peeling behavior or compromise the adhesion between the MOF and its interfaced layer.…”
Section: Discussionmentioning
confidence: 99%
“…While fixed beds are often utilized to evaluate MOF separation performance in laboratory environments, monoliths are more practical solutions due to their improved mass and heat transfer characteristics and lower pressure drops at high flow rates . Amine‐functionalized MOF films of mmen‐M 2 (dobpdc) (M = Mg and Mn) supported on monolith contactor substrates have been investigated for CO 2 capture from simulated flue gas, and producing MOF coatings with suitable mechanical adhesion properties to withstand the activation heating treatment was found to be a challenge . In this regard, the low coefficient of thermal expansion of cordierite makes it an attractive material for monoliths to help avoid film delamination issues similar to those shown in Figure b.…”
Section: Mechanical Property Implications For Mof‐enabled Technologiesmentioning
confidence: 99%
“…[18,19] On the basis of the obtained results,i tw as concluded that al ayer-by-layer (LBL) methodf ollowed by as econdary growth step is as uitable coating method for MOF-74 film, whereas for UTSA-16 in situ dip-coating was found to be ab etter coating procedure that yields higher MOF loading. Theg rowth of amine-functionalized Mg 2 (dobpdc)o na-alumina wash-coated cordierite monolith was attempted by Darunte et al [20] through seedingo ft he monolith surfacew ithM gO first, then con-vertingittoM g 2 (dobpdc) in as ubsequent step.…”
Section: Introductionmentioning
confidence: 99%